The importance of living in Polis since school: how to do it? - Lucchetti Campos, Sara (2023)
This article is grounded in qualitative research conducted for my undergraduate thesis, focusing on the "Comprehensive Happy Schools (CHS)" model based on UNICEF's Child-Friendly Schools approach. This research identifies the factors that foster authentic engagement within the Educational Institution (EI), considering its role in citizen formation. In this context, the concept of authentic engagement is defined, along with the essential factors for its promotion, and the means to cultivate a community perspective at the local level through the exploration of public matters. I reference living in Polis because the premise is rooted in the understanding that we exist within an ecosystem requiring the alignment of social imaginaries that enable viewing the student as a political entity. The EI holds a significant responsibility in addressing environmental issues. This approach aims for students to adopt a critical perspective and engage democratically. It is noteworthy that the EI is not isolated; within the ecosystem, other entities like the Local Government are equally significant. Ultimately, its reading sheds light on the challenges and windows of opportunity for designing Local Educational Projects and the role of the Ministry of Education in that process. It addresses normative challenges and weaknesses in involving all educational stakeholders in support of students' civic education. Lastly, it examines the sustainability of experiences such as the CHS model.